1994
DOI: 10.1055/s-0038-1642389
|View full text |Cite
|
Sign up to set email alerts
|

Ticlopidine Facilitates the Deaggregation of Human Platelets Aggregated by Thrombin

Abstract: SummaryNormal human platelets aggregated by thrombin undergo the release reaction and are not readily deaggregated by the combination of inhibitors hirudin, prostaglandin E1 (PGE1) and chymotrypsin. Released adenosine diphosphate (ADP) plays an important role in the stabilization of thrombin-induced human platelet aggregates. Since ticlopidine inhibits the platelet responses to ADP, we studied thrombin-induced aggregation and deaggregation of 14C-serotonin-labeled platelets from 12 patients with cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Activation of the G q pathway through P2Y 1 leads to platelet shape change and rapidly reversible aggregation, while activation of the G i pathway through P2Y 12 elicits a slowly progressive and sustained PA not preceded by shape change. In addition to its role in ADP-induced PA, P2Y 12 mediates (i) the potentiation of platelet secretion by ADP, which is independent of the formation of large aggregates and thromboxane A 2 synthesis [3,4] and (ii) the stabilization of thrombin-induced platelet aggregates [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the G q pathway through P2Y 1 leads to platelet shape change and rapidly reversible aggregation, while activation of the G i pathway through P2Y 12 elicits a slowly progressive and sustained PA not preceded by shape change. In addition to its role in ADP-induced PA, P2Y 12 mediates (i) the potentiation of platelet secretion by ADP, which is independent of the formation of large aggregates and thromboxane A 2 synthesis [3,4] and (ii) the stabilization of thrombin-induced platelet aggregates [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This effect was independent of the concentrations of extracellular Ca 2+ and of the formation of large platelet aggregates and was not inhibited by acetylsalicylic acid [4,40,41]. P2Y 12 plays an essential role in the stabilization of platelet aggregates induced by thrombin [5][6][7] or TXA 2 [42]. P2Y 12 R is an important cofactor of platelet aggregation and secretion induced by several agonists (Fig.…”
Section: Role Of P2y 12 R In Platelet Responses To Agonists Other Thamentioning
confidence: 99%
“…When ADP is secreted by platelet dense granules upon stimulation by secretioninducing agonists, it amplifies the platelet responses [3,4], stabilizes platelet aggregates [5][6][7], and contributes to the procoagulant activity of platelets [8]. The secretion of platelet dense granules constituents and the ensuing secondary aggregation that are sometimes observed following stimulation with ADP of normal platelet-rich plasma (PRP) are triggered by thromboxane (Tx) A 2 , whose synthesis is stimulated by platelet aggregation and not by ADP [9,10].…”
Section: +mentioning
confidence: 99%
“…27 This effect, which is probably mediated by PI3K, 18,28 was observed both at physiologic and micromolar concentrations of extracellular Ca 2ϩ , in the presence of acetylsalicylic acid (ASA), and independently of the formation of large platelet aggregates, demonstrating that it is a direct effect of P2Y 12 , rather than secondary to P2Y 12 -mediated amplification of aggregation. [24][25][26] P2Y 12 plays an essential role in the stabilization of platelet aggregates induced by thrombin [3][4][5] or thromboxane A 2 (Figure 2), 29 which is mediated by PI3K. 14 Studies of human platelets congenitally lacking P2Y 12 and of P2Y 12 knockout mice demonstrated that platelet aggregation and secretion induced by a range of platelet agonists were impaired.…”
Section: In Platelet Functionmentioning
confidence: 99%